Characterization of serum and urinary chromogranin A by size exclusion chromatography: Impact on calibrator selection and urinary assay - Tsao, K.‐C. (J Clin Lab Anal, 2001)
Serum chromogranin A (CgA) is a useful marker for neuroendocrine tumors and is detectable in carcinomas at advanced stages. Elevated serum CgA is also an indicator of poor prognosis in prostate cancer and is useful for predicting the failure of hormonal therapy for prostate cancer patients. We found that CgA molecules with three different sizes could be detected in normal human serum. However, only the largest CgA molecule appears in patients with liver disease. Serum taken from cancer patients is composed predominantly of the middle‐sized molecule, whereas the smallest CgA molecule was elevated in serum drawn from renal patients. Moreover, only the smallest CgA molecule was found in urine. We believe that the largest CgA molecule is metabolized by the liver, whereas the smallest CgA molecule is removed from the blood circulation via the kidney. Because the medium‐sized CgA is the dominant molecule in both the cell medium of the tumor cell line SK‐N‐AS and sera from patients with malignant diseases, CgA from the cell medium was selected as the calibrator for the CgA ELISA assay. Our findings also suggest that it would not be possible to measure the urinary CgA to reflect the serum CgA concentration in order to detect pheochromocytoma among patients with hypertension. J. Clin. Lab. Anal. 15:193–198, 2001. © 2001 Wiley‐Liss, Inc.